Digitalisasi Informasi Manajemen Aset sebagai Sarana Penunjang Operasional Kampus Menggunakan Metode Relational Unified Process - Haryanto, Abel; Sudarman, La; Sarimuddin, Sarimuddin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
Campus asset management is the processing of operational supporting infrastructure on campus. So far, the asset management system at the Baubau Polytechnic Campus still uses the conventional method, namely by recording through albums and control cards attached to the walls of each room. This method is prone to loss of assets because it is not controlled. For this reason, software for digitizing asset management information is needed using the Relational Unified Process (RUP) system development method. The approach of this method is iterative and use case driven which focuses on solving asset management problems. This system works to control in real time the process of borrowing or transferring assets. this system is very helpful for the Baubau Polytechnic Campus in managing assets, especially on the problem of losing assets. This system also provides information about the physical condition of assets in each room so that it can assist the Asset Technical Implementation Unit (UPT) to transfer assets so that campus operations can run optimally.